2008
DOI: 10.1007/s10585-008-9225-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of invasion specific splice variants of the cytoskeletal protein Mena present in mammary tumor cells during invasion in vivo

Abstract: We have studied the gene expression pattern of invasive primary mammary tumor cells using a unique in vivo invasion assay that isolates the invasive tumor cells by chemotaxis. One of the genes upregulated in the invasive tumor cells is Mena, an actin binding protein involved in the regulation of cell motility. There are multiple known splice variants of Mena accounted for by four alternatively included exons, +, ++, +++ and 11a. Using the in vivo invasion assay in rats and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 22 publications
8
145
0
Order By: Relevance
“…However, our data that the presence of hMENA 11a (ESRP1 induced) reduces the number and the length of filopodia projecting into the gel in 3D cultures (Fig. 4), is consistent with the hypothesis that the 21-aa insertion of the 11a exon, influences the ability of the Ena/VASP tetramer to promote filopodia formation and extension (11). In a xenograft rodent mammary cancer model, the invasive cancer cells showed a decrease of Mena 11a and an increase of Mena INV isoform expression (11), reminiscent of our data.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, our data that the presence of hMENA 11a (ESRP1 induced) reduces the number and the length of filopodia projecting into the gel in 3D cultures (Fig. 4), is consistent with the hypothesis that the 21-aa insertion of the 11a exon, influences the ability of the Ena/VASP tetramer to promote filopodia formation and extension (11). In a xenograft rodent mammary cancer model, the invasive cancer cells showed a decrease of Mena 11a and an increase of Mena INV isoform expression (11), reminiscent of our data.…”
Section: Discussionsupporting
confidence: 89%
“…S2A). Given the data in rodent models linking Mena splicing with mammary tumor cell invasion and migration (11,12), we performed isoform-specific overexpression and hMENA siRNA experiments to evaluate the role of alternative splicing of hMENA in human breast cancer invasion and progression. Transfection of hMENAΔv6 into BT549, MDA-MB-231, and DAL cells appreciably increased their invasiveness (Fig.…”
Section: Molecular Cloning and Characterization Of A Unique Hmena Splicementioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that hMena may augment the invasive capacity of cancer cells. Furthermore, Philippar et al reported that Mena and its isoform MenaINV can promote carcinoma cell motility and invasiveness in vivo and in vitro, and increase lung metastasis by potentiating EGF-induced membrane protrusion and increasing the matrix degradation activity of tumor cells (21,22). These reports are consistent with our previous results, and we speculate that our immunohistochemical analysis partly detected the invasive isoform of hMena.…”
Section: Discussionsupporting
confidence: 92%
“…Lpd plays an important role in membrane protrusion through downstream action of Ena/VASP, 33,78 and among the different Ena/VASP proteins, at least, Mena has been shown to be a critical player in breast cancer invasion and metastasis. [79][80][81][82][83] Thus, controlling Lpd-Ena/VASP recruitment to the leading edge clearly seems to be an attractive mechanism to regulate breast cancer cell motility which Pfn1-deficient condition takes advantage of.…”
Section: Actin-independent Function Of Pfn1 In Cell Motilitymentioning
confidence: 99%